The EFFECT OF BASIC LIFE SUPPORT APPLICATIONS ON INCREASING SELF EFFICACY IN NURSING STUDENTS - Nadia Oktiffany Putri; Retno Winarti; Ajeng Dwi Retnani (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2024)
Background: Early treatment that is not carried out is one of the causes of morbidity and mortality in victims of cardiac and respiratory arrest. Basic Life Support (BLS) knowledge and skills are important to help someone experiencing a life-threatening condition. Nursing students are one of the individuals who often face emergency conditions when they go to the hospital. An effort to overcome nursing students' understanding of BHD is by providing BHD learning. Purpose: The aim of this study was to analyze the effect of learning using the BHD application model on increasing self-efficacy in nursing students. Methods: This study was a true experimental study with a pretest-posttest control group design. The population was 198 nursing students. The instrument used in this research was developed by researchers based on a modification of the questionnaire in one of the previous studies. Result: The results of the study showed that respondents' self-efficacy increased after BLS learning. A significant increase in self-efficacy occurred in the intervention group by providing the application as a BHD learning media. Implication: The use of BLS learning methods by utilizing technological advances will make learning more compatible with context and has the potential to have a greater impact on nursing students' self-efficacy.